The mutual embodiment of landscape and livelihoods: an environmental history of Nqabara - De Klerk, Henning (Rhodes University, Faculty of Science, Department of Environmental Science, 2007)
This thesis presents a history of the landscape of Nqabara, an administrative area in a rural and coastal area of the Eastern Cape Province, South Africa. In the process of investigating landscape history, the inquiry engages with a range of data sources from diverging discursive contexts, including data from ethnographic fieldwork, from the consultation of archival documents and historical reports as well as from comparative historic and ethnographic research, necessitating a critical consideration of the epistemological contexts of data production and the dialogue between researcher and data. Furthermore, in its aim to move beyond historical description towards explanation, the study interrogates the dualist ontological conceptualisations of nature and culture, society and ecology, object and meaning upon which are built three dominant conceptual frameworks concerned with human-environment relationships: social-ecological systems theory, transdisciplinary landscape studies and political ecology. Drawing primarily upon the works of James Gibson, Anthony Giddens and Tim Ingold, an ontological foundation is developed to guide the enquiry and move towards an alternative understanding of the relationship of people's livelihoods with respect to the landscape in which it is lived, which I call here the praxisembodiment perspective. This ontology takes the situated patterns of action of a situated agent-in-its-environment as its point of departure and proceeds to develop a framework explaining how relations among the patterns of action of different agents-in-their-environment, emerge in structures that simultaneously enable and constrain future action. The foundation is thereby provided for a monist understanding of how landscape and social structure emerge simultaneously from the complex intersection of patterns of actions and interactions of agents in their environment. This framework calls for an understanding of time, space and scale, not as independent variables influencing process and action, but as emergent properties arising from the patterns of actions of situated agents. Finally the alternative ontology is applied to the history of landscape and livelihoods of people of Nqabara. It is concluded that an appropriate understanding and explanation of the critical transformations in the landscape as well as in social institutions, should be sought through analysis of the complex ways in which patterns of action of multiple spatial and temporal rhythms and between multiple agents in an environment, intersect and resonate.
Keywords: Land reform -- South Africa -- Eastern Cape; Human ecology -- South Africa -- Eastern Cape; Human beings -- Effect of environment on -- South Africa -- Eastern Cape; Land use -- Environmental aspects -- South Africa -- Eastern Cape; Landscapes -- Social aspects -- South Africa -- Eastern Cape; Landscape ecology -- South Africa -- Eastern Cape; Land use, Rural -- South Africa -- Eastern Cape; Rural development -- South Africa -- Eastern Cape